ANTECEDENTS OF TURNOVER INTENTION AND THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS A MEDIATOR IN TRAVEL AGENT EMPLOYEES IN INDONESIA - Septi Wahyuningsih; Bahtiar Usman; Dita Oki Berliyanti (INJOSEDU: International Journal of Social and Education, 2026)
This study was conducted to analyze the influence of workplace friendship, work stress, and psychological empowerment on turnover intention in travel agent companies in Indonesia, mediated by organizational citizenship behavior. This study used a quantitative approach with 1,020 respondents as the main subject who are the members of the Association of The Indonesian Tours and Travel Agencies (ASITA) and have worked for more than 3 months. Cross-sectional and one-shot data collection is conducted through the distribution of questionnaires in the form of Google Forms. The proposed model includes 10 hypotheses which are tested using Structural Equation Modeling (SEM). The majority of respondents are women aged 25–34 years, with high school education, 1–5 years of work experience, and working in the front office division. The results show that workplace friendship and psychological empowerment have a significant positive effect on organizational citizenship behavior, while work stress had a significant positive effect on turnover intention. Organizational citizenship behavior does not act as a mediating variable. This study proposes the concept of mission power in the job (MPJ) as the meaning of work that can reduce turnover intention. In addition, the effectiveness of workplace friendship is strengthened through teamwork communication (TWC), while time load, mental effort load, and psychological load are the main sources of work stress for travel agent employees